Development of software for measuring brain amyloid accumulation using 18F‐florbetapir PET and calculating global Centiloid scale and regional Z‐score values - Hiroshi Matsuda; Tsutomu Soma; Kyoji Okita; Yoko Shigemoto; Noriko Sato (Brain and Behavior, 2023)
Abstract Background and purpose Quantitative measures have been proposed to aid the visual interpretation of amyloid PET. Our objective was to develop and validate quantitative software that enables calculation of the Centiloid (CL) scale and Z‐score for amyloid PET with 18F‐florbetapir. Methods This software was developed as a toolbox in statistical parametric mapping 12 running on MATLAB Runtime. For each participant's amyloid PET, this software calculates the CL scale using the standard MRI‐guided pipeline proposed by the Global Alzheimer's Association Interactive Network (GAAIN) and generates a Z‐score map for comparison with a new amyloid‐negative database constructed from 20 healthy controls. In 23 cognitively impaired patients with suspected Alzheimer's disease, Z‐score values for a target cortical area from the new database were compared with those from the GAAIN database constructed from 13 healthy controls. The CL values obtained using low‐dose CT of PET/CT equipment were then compared with those obtained using MRI. Results The CL calculation was validated with the 18F‐florbetapir dataset in the GAAIN repository. Z‐score values obtained from the new database were significantly higher (mean ± standard deviation, 1.05 ± 0.77; p < .0001) than those obtained from the GAAIN database. The use of low‐dose CT provided CL scales that were highly correlated with those obtained with MRI (R2 = .992) but showed a slight yet significant underestimation (−2.1 ± 4.2; p = .013). Conclusions Our quantification software provides the CL scale and Z‐score for measuring overall and local amyloid accumulation with the use of MRI or low‐dose CT.